PUBLIC PARTICIPATION IN INDONESIA'S DEFENSE POLICY: CHALLENGES AND OPPORTUNITIES FOR BUILDING NATIONAL TRUST - Sarjito, Aris (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Public participation is a vital aspect of democratic governance, promoting transparency, accountability, and trust between governments and citizens. In Indonesia, public engagement in defense policymaking has been limited, often hindered by bureaucratic rigidity, lack of transparency, and societal perceptions that defense is an elite domain. This study explores the challenges and opportunities for fostering public participation in defense policymaking, focusing on its potential to strengthen trust and enhance policy legitimacy. Using a qualitative approach with secondary data, the research analyzes policy documents, government reports, and scholarly literature to uncover key patterns and insights. The findings highlight significant barriers, such as hierarchical bureaucratic structures, restricted access to information, and a general lack of public connection to defense issues. However, the study also identifies promising opportunities to enhance engagement, including leveraging digital platforms to reach a broader audience, collaborating with civil society and academic institutions, and adopting participatory governance models. Successful examples, such as community-driven disaster preparedness programs and participatory budgeting initiatives, illustrate the potential of inclusive approaches to build trust and improve policy outcomes. The study concludes that meaningful public participation is essential for ensuring defense policies align with societal needs and foster public trust. Addressing structural barriers and institutionalizing participatory mechanisms are key steps toward achieving this goal. These findings contribute to the growing discourse on participatory governance and provide practical recommendations for enhancing collaboration and inclusivity in defense policymaking. Keywords: accountability, defense policy, public participation, transparency, trust-building